PENGARUH PERCEIVED EASE OF USE, PERCEIVED USEFULNESS, DAN PEER INFLUENCE TERHADAP KEPUTUSAN UNTUK MENJADI NASABAH PADA BPRS MITRA HARMONI - SINGGIH YUNIARTO ERIKUNCORO (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
ABSTRACK The purpose of this study is to describe, the effect of perceived ease of use on customer decisions, the effect of perceived usefulness on customer decisions, and the influence of peer influence on customer decisions. The variables in this study are perceived ease of use, perceived usefulness, peer influence and purchase decision.This research was conducted at BPRS Mitra Harmoni, the population in this research is member/ partner of BPRS Mitra Harmoni. Samples taken as many as 50 people with simple random sampling technique. Data collection was done by distributing questionnaires using a scale of 1-10 points to measure 15 indicators. The analysis technique used is multiple linear regression with 5% significance level.The result of this research shows the equation of PD =0,249PE+0,432PU+0,219PI, where perceived ease of use variable have positive and significant effect to purchase decision, perceived usefulness have positive and significant effect to purchase decision, and peer influence have positive and significant influence to decision become a customer. It can be concluded that the independent variable has a positive and significant influence on the decision to become a customer in BPRS Mitra Harmoni. Coefficient of determination on this test result is 61,7% to purchase decision.